A future without borders? : theories and practices of cosmopolitan peacebuilding - Souffrant, Eddy M., 1959- (Value Inquiry Book Series, 2016)
A Future without Borders (FWB) offers an explanation of why the recent, but by now distant, movements of the "Occupy Wall Street" activists have repeated themselves across the globe. The book demonstrates some of the processes inherent to an adapting cosmopolitanism (a call for civility, a call for Justice, a call for a collective responsibility or accountability) that is not individualistic in nature. Until recently, the statal/national problems understood as politico-economic failures were conceived as isolated problems, failures of statal institutions that are particular to certain countries. FWB contests the Westphalian logic that explains these circumstances, as national failures and argues instead that the conditions be assessed as extensions of the global economic and ideological failures that they surely are. Contributors are: Anton Allahar, Arnold Farr, Andrew Fiala, Pierre-André Gagnon, Bill Gay, Kurtis Hagen, Linden F. Lewis, Tracey Nicholls, Richard T. Peterson, Jorge Rodriguez, Eddy M. Souffrant, and Hilbourne A. Watson.